Synthesis, Biological Evaluation and Molecular Modeling of Substituted Indeno[1,2-b]indoles as Inhibitors of Human Protein Kinase CK2 - Faten Alchab; Laurent Ettouati; Zouhair Bouaziz; Andre Bollacke; Jean-Guy Delcros; Christoph G.W. Gertzen; Holger Gohlke; Noël Pinaud; Mathieu Marchivie; Jean Guillon; Bernard Fenet; Joachim Jose; et al. (MDPI AG, 2015)
Due to their system of annulated 6-5-5-6-membered rings, indenoindoles have sparked great interest for the design of ATP-competitive inhibitors of human CK2. In the present study, we prepared twenty-one indeno[1,2-b]indole derivatives, all of which were tested in vitro on human CK2. The indenoindolones 5a and 5b inhibited human CK2 with an IC50 of 0.17 and 0.61 µM, respectively. The indeno[1,2-b]indoloquinone 7a also showed inhibitory activity on CK2 at a submicromolar range (IC50 = 0.43 µM). Additionally, a large number of indenoindole derivatives was evaluated for their cytotoxic activities against the cell lines 3T3, WI-38, HEK293T and MEF.